MARKETING OF VEGETABLES THROUGH E-COMMERCE IN BALI PROVINCE - Anak Agung Inten Trisna; I Nyoman Gede Ustriana; Gede Mekse Korri Arisena (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
BPS National Socioeconomic Survey of Province Bali in 2016 to 2017 years, explains the order of foodstuffs (staple foods) with the highest level of consumption after grains are vegetables.Marketing vegetable in the Province Bali were still conventional, compared to some regions in Java which was increasingly aggressively marketing agricultural products with e-commerce. The purpose of this study is to examine the profile of e-commerce users. This research was explained characteristics, marketing management activities on the e-commerce platform, easy of used, e-commerce adoption and business success. This research was conducted on the e-commerce platforms Facebook, Instagram, Tokopedia, and Shopee. The research sample of 30 vegetable traders using e-commerce, analyzed using qualitative descriptive methods and Partial Least Squares (PLS). The results showed that most traders had a relatively young age with a degree of undergraduate education. E-commerce can increase merchant income by applying management principles to the marketing process, payment, delivery, promotion, price, marketing targets and product standardization. The results of the study can provide recommendations to the younger generation that e-commerce of agricultural products in business is very promising.